2017
DOI: 10.1109/tie.2016.2538740
|View full text |Cite
|
Sign up to set email alerts
|

An Event-Related Potential-Based Adaptive Model for Telepresence Control of Humanoid Robot Motion in an Environment Cluttered With Obstacles

Abstract: Abstract-This paper develops an event-related potential (ERP)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…that correspond to particular cognition states [16], which can serve as natural biomarkers of the user's intention of interaction. This special characteristic of ERP has been evaluated for device control [17], target and error detection [18], [19], and so on. As a potential substitute for the "click" operation in HCI system, accumulating evidences confirmed that, when an intention of item selection emerged, negative potentials could be detected during conscious dwell time in the central [17] and parietal [20], [21] electrodes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…that correspond to particular cognition states [16], which can serve as natural biomarkers of the user's intention of interaction. This special characteristic of ERP has been evaluated for device control [17], target and error detection [18], [19], and so on. As a potential substitute for the "click" operation in HCI system, accumulating evidences confirmed that, when an intention of item selection emerged, negative potentials could be detected during conscious dwell time in the central [17] and parietal [20], [21] electrodes.…”
mentioning
confidence: 99%
“…This special characteristic of ERP has been evaluated for device control [17], target and error detection [18], [19], and so on. As a potential substitute for the "click" operation in HCI system, accumulating evidences confirmed that, when an intention of item selection emerged, negative potentials could be detected during conscious dwell time in the central [17] and parietal [20], [21] electrodes. One of the most popular paradigm in the EEG-based HCI research is P300 speller, which utilizes the uncommon event (flash of the target character) to induce P300 wave and decode user's intention [19].…”
mentioning
confidence: 99%
“…Finally, the proposed brain-controlled vehicle may provide an alternative way for some subjects who have a relatively low accuracy in using the brain-controlled vehicle developed in [ 1 ]. For other brain-controlled systems, such as telepresence controlling an NAO humanoid robot in [ 28 ], the robot moved slowly and discontinuously and was not controlled in the first perspective. The comparison between this work and the related articles is also shown below.…”
Section: Resultsmentioning
confidence: 99%
“…Although some studies explored how to use P300 potentials to control a wheelchair or humanoid robot by issuing motion control commands [ 27 , 28 ], the former are task-level controlled systems, and the latter move slowly and discontinuously. Furthermore, controlling a vehicle using EEG signals is more challenging than controlling a mobile robot since brain-controlled vehicles are more complicated due to their dynamic characteristics and travel at higher speeds [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their simple system configuration and advantages in safety and cost [3,4], electroencephalograph (EEG)-based BCIs have been extensively studied by researchers, and have been applied in medical diagnosis, disability assistance, smart homes, entertainment, and many other fields [5][6][7][8][9]. At present, commonly used EEG signals include Motor Imaging (MI) [10,11], Slow Cortical Potential (SCP) [12], Event Related Potential (ERP) [13,14], motion-onset Visual Evoked Potential (mVEP) [15,16], and Steady-State Visual Evoked Potential (SSVEP) [7,17]. Compared with other methods, the system configuration of SSVEP is simpler, and more stable signals and higher recognition accuracy can be obtained without additional training for the subjects [18,19].…”
mentioning
confidence: 99%